International Students Attraction and Retention Practices at Georgian Higher Education Institutions - Kvantaliani, Ekaterine (European Scientific Journal, ESJ, 2022)
The article discusses Georgian universities’ strategies and efforts to expand internationalization and especially international student mobility in the country. In many cases, the Georgian context is very much similar to other international cases, especially in terms of cooperation between a popular international university and one of Georgian higher education institutions or applying marketing and digital tools and developing student services at universities. The study discusses international students‘ attraction and retention practices at five Georgian higher education institutions. Especially interesting are the cases of two regional universities, which are assumed as the best regional state universities in the country. One of the universities (located in Tbilisi) participating in the research has accumulated nearly twenty years of experience recruiting oversea students. The other two are universities with innovative infrastructure oriented to expanding recruiting international students’ quota and developing teaching and research activities at the institutions. The study applied qualitative research methodology and heavily relied on the grounded theory approach. The researcher analyzed strategic development and internationalization policy documents of the universities to have a clear understanding of ongoing processes at the targeted institutions.. After analyzing official documents, the researcher started interviews with the leaders and management of the universities under the research. The grounded theory approach gave the researcher the possibility to code the interview results and analyze them.